Translation of a longitudinal survey of veterans’ well-being into action by a research-practice-policy partnership - Perkins, Daniel F.; McCarthy, Kimberly J.; Morgan, Nicole R.; Balotti, Brandon A.; Davenport, Katie E.; Aronson, Keith R.; Lockwood, William; Andros, Megan (Frontiers in Public Health, 2024)
IntroductionResearch-practice-policy partnerships are shifting the academic research paradigm toward collaboration and research-informed action at community and policy levels. In this case study, researchers partnered with philanthropic foundations to actualize data findings from a rigorous, longitudinal study.ContextIn 2016, a survey of post-9/11 military veterans began assessing veterans’ well-being in key domains: health, vocation (education and employment), finances, and social relationships. Data were collected from 9,566 veterans with three study aims: document factors affecting well-being, describe the use of transition-assistance programs and distill them into common components, and identify components associated with positive changes in veterans’ well-being.Partnership formation and prioritiesThe study evolved into a partnership among an academic applied research center and philanthropic funders to disseminate survey findings, investigate additional research questions of practical application, and help ensure public and private funds are invested in evidence-informed programs and services that support veterans’ well-being. Four RPP partnership goals were identified.Mechanisms and actionsGoal 1 included survey expansion to capture data on emerging concerns (e.g., COVID-19 impacts, educational experiences, burn pit exposure, civic engagement, social-media use). This resulted in eight waves of data collection over 6.5 years. Goal 2 involved co-interpretation of data to define successful military-to-civilian transition (MCT) and strategic communications to engage national leaders in policy change for veterans. Goal 3 focused on evaluation support of partners’ organizational portfolios and programs, which resulted in new tools such as an online screener that veteran-serving providers could use to identify veterans’ MCT risks and respond with tailored, research-informed resources and program components. Goal 4 allowed for the application of research findings with an innovative model for using longitudinal study variables within robust comparison analyses to assess partners’ program components; propensity matching demonstrated that effective component use leads to better outcomes for veterans (e.g., higher salaries).DiscussionPartnerships can equip funders and service organizations with credible data, clear messaging, and tools to advocate for and champion the well-being of populations. This partnership, galvanized by using data for co-learning and collaborative action, has augmented the nation’s understanding of veterans’ reintegration and has led to veterans receiving data-driven support for successful transitions and enhanced well-being.